Seismogenic magma intrusion before the 2010 eruption of Eyjafjallajokull volcano, Iceland - Tarasewicz, J.; White, R. S.; Brandsdóttir, B.; Schoonman, C.M. (Geophysical Journal International, 2014)
We present relatively relocated earthquake hypocentres for >1000 microearthquakes ( M L < 3) that occurred during the 2 weeks immediately prior to the 2010 March 20 fissure eruption at Fimmvörðuháls on the flank of Eyjafjallajökull volcano in Iceland. Our hypocentre locations lie predominantly in horizontally separated clusters spread over an area of 10 km2 and approximately 4 km below sea level (5 km below the surface). Seismic activity in the final 4 d preceding the eruption extended to shallower levels <2 km below sea level and propagated to the surface at the Fimmvörðuháls eruption site on the day the eruption started. We demonstrate using synthetic data that the observed apparent ∼1 km vertical elongation of seismic clusters is predominantly an artefact caused by only small errors (0.01–0.02 s) in arrival time data. Where the signal-to-noise ratio was sufficiently good to make subsample arrival time picks by cross-correlation of both P - and S -wave arrivals, the mean depth of 103 events in an individual cluster were constrained to 3.84 ± 0.06 km. Epicentral locations are significantly less vulnerable to arrival time errors than are depths for the seismic monitoring network we used. Within clusters of typically 100 recorded earthquakes, most of the arrivals exhibit similar waveforms and identical patterns of P -wave first-motion polarities across the entire monitoring network. The clusters of similar events comprise repetitive sources in the same location with the same orientations of failure, probably on the same rupture plane. The epicentral clustering and similarity of source mechanisms suggest that much of the seismicity was generated at approximately static constrictions to magma flow in an inflating sill complex. These constrictions may act as a form of valve in the country rock, which ruptures when the melt pressure exceeds a critical level, then reseals after a pulse of melt has passed through. This would generate recurring similar source mechanisms on the same weak fault plane as the ...